Pragmatic Competence as a Structural Component of Foreign Language Communicative Competence of Students - Sharipov Feruzjon Isor o'gli (International Journal on Integrated Education, 2022)
The article describes the necessity of conscious inclusion of the theory of politeness as an integral part of the formation of pragmatic competence. The features of trans-actional and interactional communication are considered, and an extension of the concept of "academic discourse" within the framework of teaching foreign languages is also proposed.